Investigation of the thermal responses under gas channel and land inside proton exchange membrane fuel cell with assembly pressure. (15th February 2022) - Wang, Qianqian; Tang, Fumin; Li, Bing; Dai, Haifeng; Zheng, Jim P.; Zhang, Cunman; Ming, Pingwen
Highlights: Two-dimensional model considering interface and compression effect is developed. Thermal responses under gas channel and land are significantly different. Interface resistances greatly affect thermal response and performance. Phase change can cause temperature overshoot/undershoot as load changes. An optimal assembly pressure is found with consideration heat transfer. Abstract: The improper thermal response is one of the main causes of proton exchange membrane fuel cell degradation. In this study, a two-dimensional, non-isothermal, two-phase transient fuel cell model has been established combined with newly measured experimental data. This model fully incorporates the land and gas channel (GC) of the bipolar plate, comprehensively accounting for the electrical contact resistance (ECR) and the thermal contact resistance (TCR) at the carbon paper/land interface, as well as the changes of carbon paper structure and electrical/thermal resistance induced by assembly pressure. By simulation, the impacts of interface resistance, working conditions, and assembly pressure on the thermal responses under land and GC are systematically investigated. The existence of TCR is found to increase the two regions' temperature significantly, while ECR only slightly raises it by generating a surface heat source. Furthermore, uneven distribution, ununiform fluctuation, and rapid overshoot/undershoot of temperature are observed in the two areas during overload and change load operations. It is mainly caused by the different distributions and responses of reaction and phase change at various locations. In the end, the average temperature is found to fall significantly and reach a new steady fastly with the increase of assembly pressure due to the reduction of bulk and interface thermal resistances of carbon paper. However, performance degradation and hot spot temperature rise are further observed if the pressure is too high. To balance performance and heat transfer, we should choose an optimal assembly pressure.